An analysis of brass casting parameter process using sand casting mold - Kamal, M. Nasrul (Opción, 2019)
This research tried to analyze the existing casting process of ganto recycled brass by varying the liquid pressure parameters of different induction metals, followed by the pouring of liquid metal into the mold. The method used in this research was descriptive qualitative with aesthetic analysis. As a result, metal casting can be defined as the process of molten metal, poured into a mold, then allowed to be cool and freeze. In conclusion, Ganto is one of the objects of brass casting that continues to produce the brass handicrafts in Jorong Kapalo Koto, especially the production center of Zikri ganto